Influence of Tamarindus indica seed nano‐powder on properties of Luffa cylindrica (L.) fruit waste fiber reinforced polymer composites. Issue 9 (10th August 2022) - Felix Sahayaraj, A.; Muthukrishnan, M.; Ramesh, M.
Abstract: The aim of this investigation is to determine the physical, mechanical, water absorption behavior, and thermal properties of Tamarindus indica seed powder (TISP) incorporated Luffa cylindrica fruit (LCF) waste fiber reinforced epoxy composites. TISP of size 40–50 nm was mixed with matrix in various weight proportions (2.5, 5.0, 7.5, and 10 wt%), and the composite laminates were made using the manual stacking followed by compression molding technique. The developed composite samples were subjected to various testing which includes density, tensile, compression, flexural, impact, hardness, and water absorption behavior. Thermo‐gravimetric analysis (TGA) was also done to investigate the influence of TISP addition on the prepared sample to determine thermal stability. The results showed inclusion of 7.5 wt% TISP resulting better physico‐mechanical and thermal properties. A field emission scanning electron microscopy (FESEM) test was conducted for the investigation of the bonding nature at the fiber/matrix interface, fiber pull‐outs, voids, and internal cracks. From the results it is seen that the addition of TISP improve the performance of the developed LCF waste fiber reinforced epoxy composites. Further, these composites show better resistance to moisture, which could have implications in automobile and structural applications. Abstract : The significance of Tamarindus indica seed powder on the properties of Luffa cylindrica fruit (LCF) outer layer waste fiber reinforced polymer composites have been investigated. The results showed that the addition of Tamarindus indica seed powder up to 7.5% during composite processing improves the overall performance of developed composites.